A Naturalistic Study of Driving Behavior in Older Adults and Preclinical Alzheimer Disease: A Pilot Study. (February 2019) - Babulal, Ganesh M.; Stout, Sarah H.; Benzinger, Tammie L. S.; Ott, Brian R.; Carr, David B.; Webb, Mollie; Traub, Cindy M.; Addison, Aaron; Morris, John C.; Warren, David K.; Roe, Catherine M.
A clinical consequence of symptomatic Alzheimer's disease (AD) is impaired driving performance. However, decline in driving performance may begin in the preclinical stage of AD. We used a naturalistic driving methodology to examine differences in driving behavior over one year in a small sample of cognitively normal older adults with ( n = 10) and without ( n = 10) preclinical AD. As expected with a small sample size, there were no statistically significant differences between the two groups, but older adults with preclinical AD drove less often, were less likely to drive at night, and had fewer aggressive behaviors such as hard braking, speeding, and sudden acceleration. The sample size required to power a larger study to determine differences was calculated.